Developing Quizizz-Based Vocabulary Materials for Junior High School Students Using the ADDIE Model - Muna Mawaddah; Diana Rosa Agustina; Selnistia Hidayani (Jurnal Intelek Dan Cendikiawan Nusantara, 2025)
This study explores the development of Quizizz-based vocabulary materials for junior high school students using the ADDIE instructional design model. The ADDIE model comprising Analysis, Design, Development, Implementation, and Evaluation provides a systematic approach to creating effective learning materials. The research focuses on how each phase of ADDIE can be applied to design interactive and engaging vocabulary lessons using Quizizz, a gamified digital platform. The study emphasizes the importance of conducting a thorough analysis of students’ needs, designing content that aligns with curriculum goals, and developing quizzes that incorporate multimedia elements for enhanced learning. The materials are implemented in the classroom and evaluated based on student performance and engagement. Findings suggest that the combination of the ADDIE model and Quizizz enhances students’ vocabulary retention, motivation, and participation. The results also show the potential of digital game-based learning in language education, especially in increasing student engagement and learning outcomes.